Industrial training report: Kompleks Nasyrul Quran / Muhammad Izham Haiqal Mohd Zamzuri - Mohd Zamzuri, Muhammad Izham Haiqal (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report outlines the industrial training experience of an Assistant Module Advisor at Nasyrul Quran, focusing on the responsibilities and skills developed during the internship. The training involved assisting in the creation of educational modules, preparing promotional materials, managing event logistics, and maintaining proper documentation. The intern worked closely with different departments such as IT, Tashih, and Academy, ensuring smooth coordination and implementation of Personaliti Quran programs. Key learning outcomes included improved time management, teamwork, and communication skills. The report also provides recommendations for enhancing the organization's information management practices, specifically through better documentation systems and improved mentoring structures. Overall, the internship provided valuable insights into the operational processes at Nasyrul Quran and contributed to the personal and professional growth of the intern.